Alloying Nickel with Molybdenum Significantly Accelerates Alkaline Hydrogen Electrocatalysis. Issue 11 (26th January 2021) - Wang, Miao; Yang, Hao; Shi, Jinan; Chen, Yufeng; Zhou, Yuan; Wang, Liguang; Di, Sijia; Zhao, Xuan; Zhong, Jun; Cheng, Tao; Zhou, Wu; Li, Yanguang
Abstract: Bifunctional hydrogen electrocatalysis (hydrogen‐oxidation and hydrogen‐evolution reactions) in alkaline solution is desirable but challenging. Among all available electrocatalysts, Ni‐based materials are the only non‐precious‐metal‐based candidates for alkaline hydrogen oxidation, but they generally suffer from low activity. Here, we demonstrate that properly alloying Ni with Mo could significantly promote its electrocatalytic performance. Ni4 Mo alloy nanoparticles are prepared from the reduction of molybdate‐intercalated Ni(OH)2 nanosheets. The final product exhibits an apparent hydrogen‐oxidation activity exceeding that of the Pt benchmark and a record‐high mass‐specific kinetic current of 79 A g −1 at an overpotential of 50 mV. A superior hydrogen‐evolution performance is also measured in alkaline solution. These experimental data are rationalized by our theoretical simulations, which show that alloying Ni with Mo significantly weakens its hydrogen adsorption, improves the hydroxyl adsorption and decreases the reaction barrier for water formation. Abstract : Ni4 Mo alloy nanoparticles were prepared from the reduction of molybdate‐intercalated Ni(OH)2 nanosheets. They exhibited the highest mass activity among all non‐precious‐metal‐based electrocatalysts for the hydrogen‐oxidation reaction in our best knowledge as well as a superb hydrogen‐evolution‐reaction performance in alkaline solution.